MEMAHAMI ALIRAN QURANIYAH DI KABUPATEN BANDUNG BARAT JAWA BARAT: DARI PROBLEM TEOLOGIS HINGGA EKONOMI: UNDERSTANDING QURANIYAH STREAM IN WEST BANDUNG DISTRICT OF WEST JAVA: FROM THEOLOGY TO ECONOMY PROBLEMS - Anik Farida (Penamas, 2015)
This paper presents the results of a research on the Quraniyah stream in Bandung Java as one of the cases of a religious sreams appeared in Indonesia. After the end of the New Order regime, Indonesian religious life was colored by the emergence of groups, steams, understanding and new religious movements. The study uses qualitative approach, and in-depth interviews and observations to the key figures of this stream and some poeple who close to these figures, and the parties involved to handling this stream, as a data collection. This study shows that Quraniyah stream is theologically different from Islamic doctrine mainstream. The phenomenon of the rise of the stream was motivated by local political changes, and brings sociological and economic problem of this society. Failure to socio- economic aspects have brought people to psychological problems. The emergence of Quraniyah stream is caused by psychological problems with psychiatric delusions symptoms, hallucinations and bizarre dreams. Keywords: Quraniyah, deviant group, psychology of religion, sociology of religion, Bandung. Tulisan ini menyajikan hasil penelitian tentang aliran Quraniyah di Bandung Jawa sebagai salah satu kasus kemunculan aliran keagamaan di Indonesia. Setelah berakhirnya pemerintahan Orde Baru, kehidupan keagamaan di tanah air diwarnai dengan bermunculannya kelompok, aliran, paham, dan gerakan keagamaan baru. Penelitian dilakukan dengan pendekatan kualitatif, yang pengumpulan datanya dilakukan dengan wawancara mendalam dan observasi terhadap tokoh kunci aliran ini dan beberapa masyarakat yang dekat dengan tokoh ini serta pihak-pihak yang terlibat menangani aliran ini. Penelitian ini menunjukkan, bahwa memang secara teologis berbeda dengan doktrin Islam arus utama. Fenomena munculnya aliran Quraniyah dilatari perubahan politik lokal, yang menyeret pada problem sosiologis dan ekonomi masyarakat. Kegagalan pada wilayah sosial-ekonomi menyeret individu pada masalah psikologis. Kasus aliran Quraniyah menunjukkan adanya problem psikologis dengan gejala psikiatrik delusi, halusinasi, dan mimpi aneh menjadi yang menjadi awal munculnya aliran ini. Kata Kunci: Quraniyah, aliran sesat, psikologi agama, sosiologi agama, Bandung.